2009
DOI: 10.1007/s00127-009-0124-3
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and decreased risk of substance use disorders: is the effect mediated by social support or mental health status?

Abstract: ObjectiveThe negative association between religiosity (religious beliefs and church attendance) and the likelihood of substance use disorders is well established, but the mechanism(s) remain poorly understood. We investigated whether this association was mediated by social support or mental health status.MethodWe utilized cross-sectional data from the 2002 National Survey on Drug Use and Health (n = 36,370). We first used logistic regression to regress any alcohol use in the past year on sociodemographic and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 47 publications
8
66
0
5
Order By: Relevance
“…Religious commitment and religiosity (including church attendance) have been associated with lower rates of alcohol use (Edlund et al, 2009), binge drinking, and marijuana use (White et al, 2006) among college students. Students who reported declines in their attendance at religious services also reported a corresponding increase in consumption of alcohol and marijuana (Bryant et al, 2003).…”
Section: Religious Behaviours and Health Behavioursmentioning
confidence: 99%
“…Religious commitment and religiosity (including church attendance) have been associated with lower rates of alcohol use (Edlund et al, 2009), binge drinking, and marijuana use (White et al, 2006) among college students. Students who reported declines in their attendance at religious services also reported a corresponding increase in consumption of alcohol and marijuana (Bryant et al, 2003).…”
Section: Religious Behaviours and Health Behavioursmentioning
confidence: 99%
“…Authors have been pointing out religiosity as a protective factor against the consumption of drugs, [18][19][20] reinforcing that religiosity remains a protective factor against the use of psychoactive substances, both licit and illicit. In this context, it is possible to infer that religion may represent a strength in the sense of helping the professional of the Family Health team to develop preventive actions for the community in partnership with the churches in the covered area in the planning of educational actions for health.…”
Section: 14-15mentioning
confidence: 99%
“…[1][2][3][4] Religious attendance, religious affiliation, and intrinsic religiousness have been associated with lower rates of alcohol use/abuse, binge drinking, and lifetime use of alcohol. 1,[5][6][7][8] Mullen et al 9 found that Catholics are more permissive in their attitudes, while Protestants are more likely to endorse abstinence from alcohol.…”
Section: Introductionmentioning
confidence: 99%